Evaluating Digital Zakat Platforms: Usability, Technical Performance, and Maṣlaḥah in Indonesia and Malaysia - Toto Andri Puspito; Zezen Zainul Ali; Ali Akram Kadhim; Essa Lafi Hassan Al Smadi; Hamdan Ghunemat (Nusantara: Journal of Law Studies, 2026)
Digital transformation has reshaped public services, including website-based zakat services, which have contributed to increased public participation in zakat payments. This study aims to evaluate the usability and technical performance of two zakat portals: basnaz.go.id (Indonesia) and zakat.com.my (Malaysia). This study offers a cross-national comparative approach by integrating the perspectives of usability, the right to religious information (ḥaqq al-maʿlūmāt), and maṣlaḥah (public benefit). This study uses a mixed-methods approach combining quantitative and qualitative methods, including testing website technical performance with GTMetrix and evaluating system usability with the System Usability Scale (SUS) among 10 respondents. The findings show that both portals achieved a 100% task success rate, indicating strong learnability in completing basic zakat-related tasks. However, the SUS results reveal different levels of perceived usability: baznas.go.id obtained an average SUS score of 68.25, indicating acceptable usability, while zakat.com.my obtained a score of 61.75, indicating marginal usability. In terms of efficiency, zakat.com.my showed a slightly higher Time-Based Efficiency score, whereas baznas.go.id demonstrated stronger technical performance, as indicated by GTMetrix metrics, particularly the performance score, structure score, Largest Contentful Paint, and Total Blocking Time. These findings show that digital zakat service quality cannot be assessed only through task success but must also consider user satisfaction, technical responsiveness, accessibility, and public benefit. From the perspective of maqāṣid al-sharīʿah, the digitization of zakat contributes to the realization of public benefit by facilitating zakat payments, increasing transparency and accountability in zakat fund management, and expanding access to services. This study contributes to Islamic digital governance scholarship by integrating usability testing, website performance evaluation, and maqāṣid al-sharīʿah analysis to assess digital zakat services as instruments of transparency, ḥaqq al-maʿlūmāt, and maṣlaḥah-oriented public services.